Simulation of an aircraft environmental control system - Jennions, Ian; Ali, Fakhre; Miguez, Manuel Esperon; Escobar, Ignacio Camacho (Elsevier, 2020)
The environmental control system of a civil aircraft is a major driver of maintenance. Legacy systems, such as those on the Boeing 737, are particularly at risk, as they are not instrumented for health management. These systems degrade in operation and allow compensation within their operation for degrading components, until severe degradation or failure results. The required maintenance is then both costly and disruptive. The goal of this research is to produce a simulation environment that can model the aircraft environmental control system, in order that analysis for sensor placement and algorithms can be performed without extensive, and expensive, testing. A simulation framework called Simscape Environmental Control System Simulation under All Conditions has been proposed and implemented. It offers a library of components that can be assembled into specific aircraft environmental control system simulation configurations. It is capable of simulating the health state indicating parameters at sub-system and component levels under a wide-range of aircraft operating scenarios. The developed framework has been successfully implemented to simulate a Boeing 737-800 passenger air conditioner. Its verification and validation has been carried out against the actual data corresponding to a Boeing 737-800 passenger air conditioner operating at two different cruise operating points. An extensive comparison of the simulation is presented against the data for all the passenger air conditioner components. The overall acquired results suggest that changes in the aircraft ambient conditions can have a noticeable impact on the demanded passenger air conditioner outlet temperature, and a substantial impact on the heat transfer in the primary and secondary heat exchangers. The reported simulation capability serves as a first step towards formulating an environmental control system fault simulation and diagnostic solution.